Transformasi Digital UMKM Berbasis Odoo: Studi Kasus Toko Crochet dalam Perspektif Sosiologi Agama - Melda Agnes Manuhutu; Marsanda Marsanda; Yulianti Yulianti; Brian Brian; Natasya Leuwol (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This community service activity aims to support the digital transformation of Micro, Small, and Medium Enterprises (MSMEs) through the use of an Odoo-based system, as well as explore the integration of socio-religious values in the business development process. The case study focused on Toko Crochet, a handicraft MSME located in Kampung Salak, Sorong. The participatory approach is applied through intensive training and direct mentoring to business owners, with a focus on the development and implementation of websites based on the Odoo platform. The results show that the use of digital technology such as Odoo is able to increase the effectiveness of promotions, expand market reach, and facilitate integrated transaction management. In addition to the technical aspect, this activity also examines the religious values embraced by business actors as the foundation of work ethic, such as honesty, perseverance, spiritual responsibility, and commitment to social values. Field findings show that a religious values-based approach is able to encourage more contextual acceptance of technology, as well as create harmony between technological innovation and the cultural identity of business actors. This integration is the key to creating a sustainable MSME development model, not only in terms of economy, but also in strengthening social and spiritual character. Overall, this activity emphasizes that the digitalization of MSMEs is not only a technological issue, but also a socio-cultural process that demands a holistic approach. Strengthening micro businesses through contextual and value-based digital transformation can strengthen the position of MSMEs as the driving force of the people's economy with integrity and sustainability. This result is expected to be an example of the application of technology that is rooted in local and spiritual values of the community.